Pengaruh Corporate Governance dan Likuiditas terhadap Financial Distress dengan Ukuran Perusahaan sebagai Variabel Moderasi - Nurul Khaeria; Farida Titik Kristanti (Jurnal Manajemen Indonesia, 2023)
This study aims to check whether corporate administration and liquidity to some degree, affected monetary pain, with firm size going about as a mediator between liquidity and monetary misery. Gender diversity, managerial ownership, institutional ownership, and independent commissioners were used to execute corporate governance in this study. This study's example incorporates 13 property and land organizations that were recorded on the Indonesia Stock Trade somewhere in the range of 2017 and 2021, with a sum of 65 observational data of interest. The logistic regression analytic technique and moderation regression were used in the inquiry. The findings emphasized the concurrent influence of liquidity and corporate governance on financial stress, whereby managerial ownership, institutional ownership, and independent commissioners positively influence financial distress., In contrast, gender diversity and liquidity partially do not. Firm size has no effect on the relationship between liquidity and financial distress. Keywords—Corporate Governance; Financial Distress; Firm Size; Liquidity